2019
DOI: 10.1073/pnas.1907190116
|View full text |Cite
|
Sign up to set email alerts
|

Complete reconstitution of bypass and blocking functions in a minimal artificialFab-7insulator fromDrosophila bithoraxcomplex

Abstract: Boundaries in the bithorax complex (BX-C) delimit autonomous regulatory domains that drive parasegment-specific expression of the Hox genes Ubx, abd-A, and Abd-B. The Fab-7 boundary is located between the iab-6 and iab-7 domains and has two key functions: blocking cross-talk between these domains and at the same time promoting communication (boundary bypass) between iab-6 and the Abd-B promoter. Using a replacement strategy, we found that multimerized binding sites for the architectural proteins Pita, Su(Hw), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 56 publications
1
42
0
Order By: Relevance
“…This deletion removes the recognition sequence for the LBC but retains the two dCTCF-binding sites. As previously reported (19), F8 209 blocks cross-talk between iab-6 and iab-7, similar to F8 337 ; however, it does not support bypass ( Fig. 2A).…”
Section: The Two Dctcf Sites In the Fab-8 Boundary Are Insufficient Fsupporting
confidence: 82%
See 2 more Smart Citations
“…This deletion removes the recognition sequence for the LBC but retains the two dCTCF-binding sites. As previously reported (19), F8 209 blocks cross-talk between iab-6 and iab-7, similar to F8 337 ; however, it does not support bypass ( Fig. 2A).…”
Section: The Two Dctcf Sites In the Fab-8 Boundary Are Insufficient Fsupporting
confidence: 82%
“…Although the two dCTCF sites in Fab-8 alone are not sufficient to block cross-talk between iab-6 and iab-7, we found that a multimer containing four dCTCF (CTCF ×4 ) sites displayed near-complete blocking activity (19). To determine the minimal number of dCTCF sites necessary to block cross-talk between iab-6 and iab-7 activity, we generated a CTCF ×3 replacement ( Fig.…”
Section: Three Dctcf Sites Are Not Sufficient To Generate Blocking Acmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the proximal Fab-8 sequences are needed for the bypass activity of the Fab-8 boundary. Since we have found that dHS1 has bypass activity when combined with multimerized dCTCF or Pita sites (Kyrchanova et al 2019), we wondered whether dHS1 would be able to substitute for the proximal region of Fab-8 and rescue the bypass defects of F8 . To test this, we combined dHS1 with F8 129-337 .…”
Section: Resultsmentioning
confidence: 99%
“…To interact productively with the Abd-Bm promoter, these regulatory domains must be able to circumvent the blocking activity of the intervening boundary elements. That the presence of these intervening boundaries is problematic was illustrated by experiments in which Fab-7 was replaced by a series of heterologous boundaries including scs, Mcp, and multimerized binding sites for the chromosome architectural proteins CCCTC-binding factor (dCTCF) and Pita (Hogga et al 2001;Iampietro et al 2008;Kyrchanova et al 2016Kyrchanova et al , 2019. In all of these cases, the heterologous boundaries were able to block cross talk between iab-6 and iab-7 just like Fab-7; however, they failed to support bypass.…”
mentioning
confidence: 99%